Identifying the attributes of a profession in the practice and regulation of fire safety engineering. (May 2021) - Lange, David; Torero, Jose L.; Osorio, Andres; Lobel, Nate; Maluk, Cristian; Hidalgo, Juan P.; Johnson, Peter; Foley, Marianne; Brinson, Ashley
Abstract: Fire Safety Engineering is often implemented within a framework that requires a recognized and recognizable profession. This article reviews the current state of various attributes that define Fire Safety Engineering as a profession. It is argued that: 1) reliance on prescriptive solutions opens the domain to practitioners that do not possess the required specialist knowledge; 2) the fire safety engineering process is often triggered through non-compliances to individual prescriptive provisions, negatively impacting on the discipline's professional authority; 3) the discipline operates in a manner that exposes it to challenges of its ethical code; and 4), the lack of a well-defined accreditation framework challenges the professional culture. The resulting environment favours a customer relationship between those commissioning the work and the Fire Safety Engineer, rather than the client relationship necessary for professional practise. Most engineering disciplines respond to failures by formalisation of the profession around its duty of care to society. Conversely, in Fire Safety Engineering such responses have focused on regulation. Recent incidents are a significant impetus and opportunity for the fire safety profession to better formalize itself. Highlights: A profession is identifiable through the possession of various attributes. This paper explores some of the evidence of these attributes in the practice of Fire Safety Engineering. There is a need for Fire Safety Engineering to formalize the definition of itself as a profession.